PERSON DEIXIS AND SPATIAL DEIXIS OF KING DANGDUT BY RHOMA IRAMA SONGS - Yen Yen Natalia; Iman Santoso (IKIP Siliwangi, 2020)
The aims of this research to find deixis and spatial deixis used of song lyrics from King of Dangdut by Rhoma Irama. Descriptive qualitative method used to collect the data. The classified into type of deixis on the own criteria and the findings that the types of deixis like person deixis and spatial deixis used song lyrics of Rhoma irama. From the result, it can be concluded that person deixis and spatial deixis of finding and discussion is found in all song lyrics, personal deixis is the most being founding 81 words that is the word “Aku, Daku, Ku, Kamu, Mu, and Nya, dominate all songs. The position is the spatial deixis 20 words. It can be seen of the result analysis person deixis and spatial deixis can be many found in the six-song lyrics. Keywords: Person deixis, Spatial deixis, Music